The use of Sesbania (Sesbania rostrata) and urea in lowland rice production in Sierra Leone - Bar, A.R.; Baggie, I.; Sanginga, N. (2000)
The suitability of sesbania (Sesbania rostrata) as green manure for lowland rice was evaluated in the Inland Valley Swamp (IVS) of Sierra Leone, and attempts were made to identify appropriate methods of its management in combination with urea. Sesbania — rice intercropping and sesbania — rice rotation treatments were compared with 60 kg N ha−1 applied in two splits and 30 kg N ha−1 as basal or top dressed to rice grown in the two cropping systems. The 15N isotope dilution technique was used to quantify N uptake from the green manure and urea and its utilization by rice. Rotating 40–50 days old sesbania two days prior to transplanting and top dressing with 30 kg N ha−1 as urea at nine weeks after transplanting gave highest rice grain yield (121% over the control without sesbania and urea). However intercropping sesbania with rice tended to increase N uptake and N fertilizer utilization more than the rotation treatments. The higher grain yield of rice in rotation despite lower N uptake than intercropping shows that other effects than only N explain the beneficial effect of sesbania on rice.